Does size matter? Bailouts with large and small banks - Dávila, Eduardo; Walther, Ansgar (Journal of Financial Economics, 2020)
We explore how large and small banks make funding decisions when system-wide bailouts are possible. We show that bank size, purely on strategic grounds, is a key determinant of banks’ leverage choices, even when bailout policies treat large and small banks symmetrically. Large banks leverage more than small banks because they internalize that their decisions directly affect bailout policies. In equilibrium, this effect is amplified by strategic spillovers to small banks since banks’ leverage choices are strategic complements. Overall, the presence of large banks makes bailouts more likely. The optimal regulation features size-dependent policies that disproportionately restrict large banks’ leverage.